Preparation process of polymer modified carbonized gelling material based grouting material

By using polymer-modified carbonized gelled material-based grouting material preparation process, the problem of the existing grouting materials being reduced after the service time is extended, achieving high strength and excellent toughness and Low carbon emission grouting effect.

CN118724555BActive Publication Date: 2025-02-14ZAOZHUANG MINING GRP ZHONGXING JIANAN ENG CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411145197.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-20
Publication Date
2025-02-14
Estimated Expiration
2044-08-20

AI Technical Summary

Technical Problem

The strength and toughness of existing grouting materials have been significantly reduced after the service time is extended, and the cement-based grouting materials have a long solidification time and poor anti-dynamic water dispersion performance, making it difficult to adapt to the dynamic deformation of underground structures.

Method used

The preparation process of polymer-modified carbonized gelling material-based grouting material is adopted. By continuously stirring raw materials such as steel slag powder and dicalcium silicate in water dissolved with carbon dioxide, the in-situ carbonized modified gelling material is formed, and It is coated with polymer through polymerization, and finally components such as ettringite whiskers are added to form a mixture and ground into a grouting material.

Benefits of technology

The degree of carbonization reaction and carbon sequestration of the grouting material is improved, its strength and toughness are enhanced, the setting time is shortened, the crack resistance is improved, and carbon emissions are reduced, thus realizing the preparation of low-carbon grouting material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118724555B_ABST
    Figure CN118724555B_ABST
Patent Text Reader

Abstract

The present invention discloses a preparation process of a polymer-modified carbonized cementitious material-based grouting material, comprising the following steps: (1) adding at least one of steel slag powder, dicalcium silicate, calcium silicate stone, etc. to water dissolved with carbon dioxide for continuous stirring treatment to obtain a dispersion containing an in-situ carbonized modified cementitious material. (2) adding a polymerization reaction monomer, an initiator, and a cross-linking agent to the dispersion for polymerization reaction, and after completion, evaporating the water in the system to obtain a polymer-coated in-situ carbonized modified cementitious material. (3) adding the cementitious material to water for infiltration, and then adding calcium sulfoxide whiskers, silicate cement clinker, and gypsum to mix evenly to form a wet material, and grinding it to obtain the polymer-modified carbonized cementitious material-based grouting material. The process of the present invention not only solves the problem that the organic-inorganic composite is difficult to coordinate and affects the performance of the grouting material, but also obtains a negative carbon grouting material, which helps to reduce carbon emissions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of grouting material preparation, and in particular to a preparation process of a polymer-modified carbonized gelling material-based grouting material. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] With the rapid development of economy, the engineering field is constantly expanding, and grouting reinforcement technology is widely used in underground structural engineering, such as tunnel engineering, mining goaf and soft soil foundation treatment. Grouting plugging and reinforcement is an effective solution to control the safety of underground structural engineering, among which the structural design and performance regulation of grouting materials are the key core of grouting technology.

[0004] At present, the organic grouting materials commonly used in engineering are expensive and have poor durability. Their strength and toughness will decrease significantly with the extension of service time, which weakens the reinforcement effect. Cement-based grouting materials have a long setting time, poor anti-dynamic water dispersion performance, high rigidity, low toughness, easy cracking, and difficulty in adapting to the dynamic deformation of underground structures. Since then, organic-inorganic composite grouting materials represented by cement-based slurry compounded with water glass or polyurethane have gradually entered people's field of vision.

[0005] Organic-inorganic composite grouting materials can effectively give play to the advantages of cement slurry materials such as wide sources, low cost, high later strength, good durability, and chemical slurry materials such as good pourability and fast consolidation, and give play to their respective advantages, and have good application prospects. However, conventional organic-inorganic composite grouting materials simply mix cement slurry with organic solvents, and cannot achieve uniform dispersion of the two. In addition, organic matter will hinder the hydration of cement, reduce strength development, and cause the mechanical properties of grouting materials to fail to achieve the expected effect. Summary of the invention

[0006] In view of the above problems, the present invention provides a preparation process of a polymer-modified carbonized gelling material-based grouting material, which not only solves the problem that the organic-inorganic material composite is difficult to coordinate and affects the performance of the grouting material, but also obtains a low-carbon grouting material, which consumes carbon dioxide and helps to reduce carbon emissions. Specifically, the technical solution of the present invention is as follows.

[0007] A preparation process of a polymer-modified carbonized gelling material-based grouting material comprises the following steps:

[0008] (1) At least one of raw materials such as steel slag powder, dicalcium silicate, and calcite is added to water containing dissolved carbon dioxide and continuously stirred to obtain a dispersion containing an in-situ carbonized modified gelling material.

[0009] (2) Adding polymerization monomers, initiators, and crosslinking agents to the dispersion, and carrying out polymerization reaction under stirring conditions, and after completion, evaporating water in the system to obtain a polymer-coated in-situ carbonized modified gelling material.

[0010] (3) The polymer-coated in-situ carbonized modified cementitious material is added into water for soaking, and then calcium sulfonate whiskers, silicate cement clinker and gypsum are added and mixed evenly to form a mixture, which is then ground to obtain the polymer-modified carbonized cementitious material-based grouting material.

[0011] Furthermore, in step (1), the mass ratio of the gelling material to water is 1:5-10. Optionally, the concentration of carbon dioxide in the water is 1-10 mg / L.

[0012] Furthermore, in step (1), the mass ratio of the steel slag powder, dicalcium silicate, and calcite is 1-2:2-4:1-3. For example, when the raw material consists of steel slag powder and dicalcium silicate, the mass ratio of the two is 1-2:2-4. When the raw material consists of steel slag powder and calcite, the mass ratio of the two is 1-2:1-3. When the raw material consists of dicalcium silicate and calcite, the mass ratio of the two is 2-4:1-3.

[0013] Furthermore, in step (1), the continuous stirring treatment time is 30 to 48 hours.

[0014] Furthermore, in step (2), the mass ratio of the polymerization reaction monomer to the in-situ carbonized modified gelling material in the dispersion is 0.1-0.2:1.

[0015] Furthermore, in step (2), the mass ratio of the polymerization reaction monomer, the initiator, and the cross-linking agent is 1-1.05: 0.012-0.015: 0.0065-0.007. Optionally, the polymerization reaction monomer includes acrylamide monomer, etc. The initiator includes at least one of ammonium persulfate, potassium persulfate, etc. The cross-linking agent includes at least one of N,N'-methylenebisacrylamide, etc.

[0016] Furthermore, in step (2), the polymerization reaction time is 4-5 hours. Optionally, the system is heated at 40-50° C. to constant weight, thereby completing the removal of moisture from the system.

[0017] Furthermore, in step (3), the mass ratio of the polymer-coated in-situ carbonized modified gelling material to water is 1:0.05-0.1.

[0018] Furthermore, in step (3), the mass ratio of the polymer-coated in-situ carbonized modified cementitious material, ettringite whiskers, Portland cement clinker, and gypsum is 1:0.02-0.05:1-1.5:0.05-0.1. Optionally, the ettringite whiskers have a length of 10-20 μm and a diameter of 1-2 μm.

[0019] Furthermore, in step (3), the polymer modified carbonized cementitious material-based grouting material is mixed evenly with water at a water-cement ratio of 0.3 to 0.4 to obtain a fluid grouting material, which can be used for grouting at locations that need to be reinforced or blocked.

[0020] Compared with the prior art, the technical solution of the present invention has at least the following beneficial effects:

[0021] Firstly, the present invention adopts water containing dissolved carbon dioxide to carbonize and modify the raw materials, which solves the problem that the carbonization efficiency is significantly reduced after the raw materials are cured and carbonized to a certain extent in the traditional carbonization box with high concentration of CO2. This is because when the raw materials of the present invention are immersed in water containing dissolved carbon dioxide, the carbonate ions therein react with the calcium ions dissociated from the surface of the raw materials to form calcium carbonate; and since the carbonate ions are free in the water and the raw materials have a porous structure, the carbonization reaction will continue, thus avoiding the problem of gradual termination of the carbonization reaction caused by the reduction of the gas CO2 permeability in the above-mentioned traditional method, thereby effectively improving the carbonization reaction degree of the raw materials, increasing the carbon fixation amount, and enhancing the strength of the cementitious material-based grouting material of the present invention.

[0022] Secondly, the present invention uses a polymer reaction to in-situ compound the above-mentioned in-situ carbonized modified cementitious material, so that the carbonized modified cementitious material is coated with the formed polymer to form a polymer-modified carbonized cementitious material-based grouting material. In this process, the calcium carbonate crystals on the surface of the cementitious material act as nucleating agents to uniformly polymerize the monomers on the surface of the cementitious material. In addition, the amide group of the polymer monomer (acrylamide) is hydrolyzed into a carboxyl group, which can react with the calcium ions released by the hydration of the silicate cement clinker to further consolidate the interaction between the organic-inorganic materials in the form of chemical bonds, thereby overcoming the disadvantages of directly adding polymers to the grouting material to affect the hydration reaction of the grouting material, resulting in the deterioration of mechanical properties (especially early strength), and solving the problem of uneven dispersion of organic-inorganic materials and mutual restriction of performance. In addition, the above-mentioned polymer-modified carbonized cementitious material-based grouting material also has the characteristics of fast and controllable grouting speed and improved flexibility and elasticity of the grouting material, thereby improving the crack resistance of the grouting material.

[0023] Again, the calcium sulfonate whiskers introduced into the grouting material of the present invention further reduce the adverse effects of the polymer on the mechanical strength of the grouting material. This is because the calcium sulfonate whiskers can not only inhibit the expansion of microcracks, prevent or delay the formation of cracks, but also serve as nucleation sites for cement hydration reactions, promote the hydration reaction, and improve the mechanical strength of the grouting material, so that the compressive strength of the grouting material obtained by the present invention can be continuously developed, and the early strength is high, the toughness is excellent, and the durability is good, which greatly reduces the amount of cement used, reduces carbon dioxide emissions, and reduces the carbon footprint of grouting materials, which is conducive to the green transformation of the industry and sustainable development. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] It should be noted that the drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention and do not constitute an improper limitation of the present invention.

[0025] Figure 1 This is a scanning electron microscope image of the polymer-modified carbonized gelling material-based grouting material prepared in the following Example 1. DETAILED DESCRIPTION

[0026] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. Unless otherwise defined, all professional and scientific terms used in the present invention have the same meaning as those familiar to those skilled in the art. The preferred implementation methods and materials described in the present invention are only for demonstration purposes. The reagents or raw materials used in the invention can be purchased through conventional channels. If there are no special instructions, the reagents or raw materials used in the present invention are used in a conventional manner in the art or are used according to the product specification. Now the technical scheme of the present invention is further described in conjunction with specific embodiments.

[0027] Example 1

[0028] A preparation process of a polymer-modified carbonized gelling material-based grouting material comprises the following steps:

[0029] (1) Steel slag powder and water containing dissolved carbon dioxide (7.2 mg / L) were mixed in a mass ratio of 1:8 and stirred continuously for 36 hours to obtain a dispersion containing an in-situ carbonized modified cementitious material.

[0030] (2) Adding polymerization monomer (acrylamide monomer), initiator (ammonium persulfate) and crosslinking agent (N,N'-methylenebisacrylamide) to the dispersion, wherein the mass ratio of the polymerization monomer, initiator and crosslinking agent is 1:0.014:0.0065, and the mass ratio of the polymerization monomer to the in-situ carbonized modified gelling material in the dispersion is 0.15:1. Then stirring for 4 hours to carry out polymerization reaction, and after completion, heating to 50°C and keeping the temperature to constant weight, a polymer-coated in-situ carbonized modified gelling material is obtained.

[0031] (3) The polymer-coated in-situ carbonized modified cementitious material is mixed with water in a mass ratio of 1:0.1 and stirred evenly, and then calcium sulfonate whiskers, 42.5 ordinary Portland cement clinker, and gypsum are added and mixed evenly to form a wet material, wherein: the mass ratio of the polymer-coated in-situ carbonized modified cementitious material, calcium sulfonate whiskers, Portland cement clinker, and gypsum is 1:0.035:1.2:0.07, and the length of the calcium sulfonate whiskers is distributed between 10 and 20 μm, and the diameter is distributed between 1 and 2 μm. The wet material is ground for 30 minutes, and then the obtained powder is mixed with water in a water-cement ratio of 0.33 and stirred evenly to obtain a fluid polymer-modified carbonized cementitious material-based grouting material.

[0032] According to the Standard for Test Methods for Physical and Mechanical Properties of Concrete (GBT 50081-2019), the test pieces made of the cementitious material-based grouting material of this embodiment (whose microscopic morphology is as follows) were Figure 1 The 3d compressive strength, 28d flexural strength and 28d compressive strength of the steel sheet (as shown) were tested, and the results were: 3d compressive strength = 23.74MPa, 28d flexural strength = 6.51MPa, 28d compressive strength = 43.12MPa.

[0033] Example 2

[0034] A preparation process of a polymer-modified carbonized gelling material-based grouting material comprises the following steps:

[0035] (1) A cementitious material (composed of steel slag powder and dicalcium silicate in a mass ratio of 1:2) and water containing dissolved carbon dioxide (10 mg / L) in a mass ratio of 1:5 were mixed and stirred continuously for 30 hours to obtain a dispersion containing an in-situ carbonized modified cementitious material.

[0036] (2) Adding polymerization monomer (acrylamide monomer), initiator (potassium persulfate), and crosslinking agent (N,N'-methylenebisacrylamide) to the dispersion, wherein the mass ratio of the polymerization monomer, initiator, and crosslinking agent is 1.05:0.015:0.007, and the mass ratio of the polymerization monomer to the in-situ carbonized modified gelling material in the dispersion is 0.1:1. Then stirring for 5 hours to carry out polymerization reaction, after completion, heating to 40°C and keeping warm to constant weight, thus obtaining a polymer-coated in-situ carbonized modified gelling material.

[0037] (3) The polymer-coated in-situ carbonized modified cementitious material is mixed with water in a mass ratio of 1:0.1 and stirred evenly, and then calcium sulfonate whiskers, 42.5 ordinary Portland cement clinker, and gypsum are added and mixed evenly to form a wet material, wherein: the mass ratio of the polymer-coated in-situ carbonized modified cementitious material, calcium sulfonate whiskers, Portland cement clinker, and gypsum is 1:0.02:1:0.05, and the length of the calcium sulfonate whiskers is distributed between 10 and 20 μm, and the diameter is distributed between 1 and 2 μm. The wet material is ground for 35 minutes, and then the obtained powder is mixed with water in a water-cement ratio of 0.3 and stirred evenly to obtain a fluid polymer-modified carbonized cementitious material-based grouting material.

[0038] According to the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GBT 50081-2019), the 3d compressive strength, 28d flexural strength, and 28d compressive strength of the specimens made of the cementitious material-based grouting material in this embodiment were tested, and the results were: 3d compressive strength = 25.08 MPa, 28d flexural strength = 7.93 MPa, and 28d compressive strength = 45.37 MPa.

[0039] Example 3

[0040] A preparation process of a polymer-modified carbonized gelling material-based grouting material comprises the following steps:

[0041] (1) A cementitious material (composed of dicalcium silicate and calcite in a mass ratio of 4:3) and water containing dissolved carbon dioxide (1 mg / L) in a mass ratio of 1:10 were mixed and stirred continuously for 48 hours to obtain a dispersion containing an in-situ carbonized modified cementitious material.

[0042] (2) Adding polymerization monomer (acrylamide monomer), initiator (ammonium persulfate), and crosslinking agent (N,N'-methylenebisacrylamide) to the dispersion, wherein the mass ratio of the polymerization monomer, initiator, and crosslinking agent is 1.03:0.012:0.0065, and the mass ratio of the polymerization monomer to the in-situ carbonized modified gelling material in the dispersion is 0.2:1. Then stirring for 4 hours to carry out polymerization reaction, after completion, heating to 50°C and keeping the temperature to constant weight, the polymer-coated in-situ carbonized modified gelling material is obtained.

[0043] (3) The polymer-coated in-situ carbonized modified cementitious material is mixed with water in a mass ratio of 1:0.05 and stirred evenly, and then calcium sulfonate whiskers, 42.5 ordinary Portland cement clinker, and gypsum are added and mixed evenly to form a wet material, wherein: the mass ratio of the polymer-coated in-situ carbonized modified cementitious material, calcium sulfonate whiskers, Portland cement clinker, and gypsum is 1:0.05:1.5:0.1, and the length of the calcium sulfonate whiskers is distributed between 10 and 20 μm, and the diameter is distributed between 1 and 2 μm. The wet material is ground for 30 minutes, and then the obtained powder is mixed with water in a water-cement ratio of 0.4 and stirred evenly to obtain a fluid polymer-modified carbonized cementitious material-based grouting material.

[0044] According to the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GBT 50081-2019), the 3d compressive strength, 28d flexural strength, and 28d compressive strength of the specimens made of the cementitious material-based grouting material in this embodiment were tested, and the results were: 3d compressive strength = 22.16 MPa, 28d flexural strength = 6.24 MPa, and 28d compressive strength = 41.92 MPa.

[0045] Example 4

[0046] A preparation process of a polymer-modified carbonized gelling material-based grouting material comprises the following steps:

[0047] (1) A cementitious material (composed of steel slag powder and calcite in a mass ratio of 2:1) and water containing dissolved carbon dioxide (1 mg / L) in a mass ratio of 1:8 were mixed and stirred continuously for 36 hours to obtain a dispersion containing an in-situ carbonized modified cementitious material.

[0048] (2) Adding polymerization monomer (acrylamide monomer), initiator (ammonium persulfate), and crosslinking agent (N,N'-methylenebisacrylamide) to the dispersion, wherein the mass ratio of the polymerization monomer, initiator, and crosslinking agent is 1:0.013:0.007, and the mass ratio of the polymerization monomer to the in-situ carbonized modified gelling material in the dispersion is 0.15:1. Then stirring for 4.5 hours to carry out polymerization reaction, and after completion, heating to 50°C and keeping the temperature to constant weight, a polymer-coated in-situ carbonized modified gelling material is obtained.

[0049] (3) The polymer-coated in-situ carbonized modified cementitious material is mixed with water in a mass ratio of 1:0.07 and stirred evenly, and then calcium sulfonate whiskers, 42.5 ordinary Portland cement clinker, and gypsum are added and mixed evenly to form a wet material, wherein: the mass ratio of the polymer-coated in-situ carbonized modified cementitious material, calcium sulfonate whiskers, Portland cement clinker, and gypsum is 1:0.04:1.3:0.06, and the length of the calcium sulfonate whiskers is distributed between 10 and 20 μm, and the diameter is distributed between 1 and 2 μm. The wet material is ground for 40 minutes, and then the obtained powder is mixed with water in a water-cement ratio of 0.38 and stirred evenly to obtain a fluid polymer-modified carbonized cementitious material-based grouting material.

[0050] According to the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GBT 50081-2019), the 3d compressive strength, 28d flexural strength, and 28d compressive strength of the specimens made of the cementitious material-based grouting material in this embodiment were tested, and the results were: 3d compressive strength = 25.57 MPa, 28d flexural strength = 8.46 MPa, and 28d compressive strength = 47.33 MPa.

[0051] Example 5

[0052] A preparation process of a polymer-modified carbonized cementitious material-based grouting material is the same as the above-mentioned embodiment 1, except that the polymer-coated in-situ carbonized modified cementitious material of this embodiment is prepared by the following method:

[0053] (1) Steel slag powder and clean water are mixed in a mass ratio of 1:8 and stirred continuously for 36 hours to obtain a dispersion containing an in-situ carbonized modified cementitious material.

[0054] (2) Adding polymerization monomer (acrylamide monomer), initiator (ammonium persulfate), and crosslinking agent (N,N'-methylenebisacrylamide) to the dispersion, wherein the mass ratio of the polymerization monomer, initiator, and crosslinking agent is 1:0.014:0.0065, and the mass ratio of the polymerization monomer to the in-situ carbonized modified gelling material in the dispersion is 0.15:1. Then stirring for 4 hours to carry out polymerization reaction, after completion, heating to 50°C and keeping warm to constant weight, thus obtaining a polymer-coated in-situ carbonized modified gelling material.

[0055] According to the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GBT 50081-2019), the 3d compressive strength, 28d flexural strength, and 28d compressive strength of the specimens made of the cementitious material-based grouting material in this embodiment were tested, and the results were: 3d compressive strength = 18.41 MPa, 28d flexural strength = 5.02 MPa, and 28d compressive strength = 35.26 MPa.

[0056] Example 6

[0057] A preparation process of a polymer-modified carbonized gelling material-based grouting material comprises the following steps:

[0058] (1) A cementitious material (composed of steel slag powder and calcite in a mass ratio of 2:1) and water containing dissolved carbon dioxide (1 mg / L) in a mass ratio of 1:8 were mixed and stirred continuously for 36 hours. The solid product was then separated and dried to remove moisture, thereby obtaining an in-situ carbonized modified cementitious material.

[0059] (2) The polymerization reaction monomer (acrylamide monomer) and the in-situ carbonized modified gelling material are mixed at a mass ratio of 0.15:1 and stirred evenly to obtain a mixture of the polymer and the in-situ carbonized modified gelling material.

[0060] (3) The mixture of the polymer and the in-situ carbonized modified cementitious material is mixed with water at a mass ratio of 1:0.07 and stirred evenly, and then calcium sulfonate whiskers, 42.5 ordinary Portland cement clinker, and gypsum are added and mixed evenly to form a wet material, wherein: the mass ratio of the polymer-coated in-situ carbonized modified cementitious material, calcium sulfonate whiskers, Portland cement clinker, and gypsum is 1:0.04:1.3:0.06, and the length of the calcium sulfonate whiskers is distributed between 10 and 20 μm, and the diameter is distributed between 1 and 2 μm. The wet material is ground for 40 minutes, and then the obtained powder is mixed with water at a water-cement ratio of 0.38 and stirred evenly to obtain a fluid polymer-modified carbonized cementitious material-based grouting material.

[0061] According to the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GBT 50081-2019), the 3d compressive strength, 28d flexural strength, and 28d compressive strength of the specimens made of the cementitious material-based grouting material in this embodiment were tested, and the results were: 3d compressive strength = 14.73 MPa, 28d flexural strength = 3.58 MPa, and 28d compressive strength = 30.19 MPa.

[0062] Example 7

[0063] A preparation process of a polymer-modified carbonized gelling material-based grouting material comprises the following steps:

[0064] The polymer-coated in-situ carbonized modified cementitious material (prepared according to the method of the above embodiment 3) was mixed with water at a mass ratio of 1:0.05 and stirred evenly, and then 42.5 ordinary Portland cement clinker and gypsum were added and mixed evenly to form a wet material, wherein: the mass ratio of the polymer-coated in-situ carbonized modified cementitious material, Portland cement clinker and gypsum was 1:1.5:0.1. The wet material was ground for 30 minutes, and then the obtained powder was mixed with water at a water-cement ratio of 0.4 and stirred evenly to obtain a fluid polymer-modified carbonized cementitious material-based grouting material.

[0065] According to the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GBT 50081-2019), the 3d compressive strength, 28d flexural strength, and 28d compressive strength of the specimens made of the cementitious material-based grouting material in this embodiment were tested, and the results were: 3d compressive strength = 22.49 MPa, 28d flexural strength = 6.06 MPa, and 28d compressive strength = 42.54 MPa.

[0066] Example 8

[0067] A preparation process of a polymer-modified carbonized gelling material-based grouting material comprises the following steps:

[0068] (1) The polymerization reaction monomer (acrylamide monomer) and steel slag are mixed in a mass ratio of 0.15:1 and stirred evenly to obtain an organic-inorganic mixture.

[0069] (2) The organic-inorganic mixture, ettringite whiskers, 42.5 ordinary Portland cement clinker, and gypsum are mixed in a mass ratio of 1:0.035:1.2:0.07 and stirred evenly, wherein the length of the ettringite whiskers is distributed between 10 and 20 μm, and the diameter is distributed between 1 and 2 μm. The obtained mixture is then mixed with water in a water-cement ratio of 0.33 and stirred evenly to obtain a cementitious material-based grouting material.

[0070] (3) The grouting material is built into the mold, demolded after hardening and forming, and then placed in a carbonization box (CO2 concentration 20±3%, humidity 90%) for carbonization curing for 3 days. The compressive strength of the specimens is then tested according to the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" (GBT 50081-2019). In addition, the specimens that have undergone the above-mentioned carbonization curing for 3 days are naturally cured to 28 days, and their flexural strength is tested according to the above-mentioned standard. The test results of the above-mentioned performance indicators are: 3d compressive strength = 13.25MPa, 28d flexural strength = 3.17MPa, 28d compressive strength = 31.82MPa.

[0071] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the above embodiments, those skilled in the art can still modify the technical solutions described in the above embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made shall be included in the protection scope of the present invention.

Claims

1. A process for preparing a polymer-modified carbonized gelling material-based grouting material, characterized in that: The steps include: (1) adding at least one of steel slag powder, dicalcium silicate and calcite stone to water containing dissolved carbon dioxide and continuously stirring the mixture to obtain a dispersion containing an in-situ carbonized modified gelling material; (2) adding polymerization monomers, initiators, and cross-linking agents to the dispersion, and performing polymerization under stirring conditions, and after completion, evaporating water in the system to obtain a polymer-coated in-situ carbonized modified gelling material; (3) adding the polymer-coated in-situ carbonized modified cementitious material into water for soaking, then adding ettringite whiskers, silicate cement clinker and gypsum to mix evenly to form a wet material, and grinding the wet material to obtain the polymer-modified carbonized cementitious material-based grouting material; In step (2), the mass ratio of the polymerization monomer, the initiator, and the cross-linking agent is 1-1.05: 0.012-0.015: 0.0065-0.007; In step (3), the mass ratio of the polymer-coated in-situ carbonized modified cementitious material, ettringite whisker, silicate cement clinker and gypsum is 1:0.02~0.05:1~1.5:0.05~0.

1.

2. The preparation process of the polymer modified carbonized gelling material based grouting material according to claim 1, characterized in that: In step (1), the mass ratio of the gelling material to water is 1:5-10.

3. The preparation process of the polymer modified carbonized gelling material based grouting material according to claim 1, characterized in that: In step (1), the concentration of carbon dioxide in the water is 1-10 mg / L.

4. The process for preparing the polymer modified carbonized gelling material based grouting material according to claim 1, characterized in that: In step (1), the mass ratio of the steel slag powder, dicalcium silicate and calcite is 1-2:2-4:1-3.

5. The process for preparing the polymer modified carbonized gelling material based grouting material according to claim 1, characterized in that: In step (1), the continuous stirring treatment time is 30 to 48 hours.

6. The process for preparing the polymer modified carbonized gelling material based grouting material according to claim 1, characterized in that: In step (2), the mass ratio of the polymerization reaction monomer to the in-situ carbonized modified gelling material in the dispersion is 0.1-0.2:

1.

7. The process for preparing the polymer modified carbonized gelling material based grouting material according to claim 1, characterized in that: In step (2), the polymerization reaction monomer includes at least one acrylamide monomer.

8. The process for preparing the polymer modified carbonized gelling material based grouting material according to claim 1, characterized in that: In step (2), the initiator includes at least one of ammonium persulfate and potassium persulfate.

9. The process for preparing the polymer modified carbonized gelling material based grouting material according to claim 1, characterized in that: In step (2), the cross-linking agent includes at least one of N,N'-methylenebisacrylamide.

10. The process for preparing a polymer-modified carbonized gelling material-based grouting material according to claim 1, characterized in that: In step (2), the polymerization reaction time is 4 to 5 hours.

11. The process for preparing a polymer-modified carbonized gelling material-based grouting material according to claim 1, characterized in that: The system was heated between 40 and 50°C to constant weight.

12. The process for preparing a polymer-modified carbonized gelling material-based grouting material according to claim 1, characterized in that: In step (3), the mass ratio of the polymer-coated in-situ carbonized modified gelling material to water is 1:0.05-0.

1.

13. The process for preparing a polymer-modified carbonized gelling material-based grouting material according to claim 1, characterized in that: In step (3), the length of the ettringite whisker is 10-20 μm and the diameter is 1-2 μm.

14. The process for preparing a polymer-modified carbonized gelling material-based grouting material according to any one of claims 1 to 13, characterized in that: In step (3), the polymer modified carbonized cementitious material-based grouting material is mixed evenly with water at a water-cement ratio of 0.3 to 0.4 to obtain a fluid grouting material.

Citation Information

Patent Citations

  • In-situ synergistic modified reinforced cement-based composite material and application thereof

    CN114436597A

  • Processes and systems for carbon dioxide sequestration and related concrete compositions

    US20210107840A1